Adverse side-effects of biological agents: Hypersensitivity reactions - Stojić-Vukanić Zorica; Arsenović-Ranin Nevena; Antić-Stanković Jelena; Milenković Marina (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
Clinical use of various biological agents (protein-based products derived from biological sources, such as bacteria, fungi or mammalian cells) have greatly improved the treatment of a wide variety of diseases in humans. Nevertheless, a variety of their adverse reactions have been observed. These adverse effects have been clasified in five types (α, β, γ, δ and ε). Type β adverse effect involves hypersensitivity reactions linked to the immunogenicity of biological agents. It is worth emphasizing that biological agents irrespective whether they contain xenoantigens may lead to development of anti-drug antibodies. Several drug-, patients-, diseaseand treatment-related factors contribute to immunogenicity of biological agents. Anti-drug antibodies can influence either the efficacy of biological agent or induce hypersensitivity reactions. One of them is immediate infusion reaction, which occurs during or within one hour after biological agent infusion. This reaction may cause mild to severe clinical manifestations. Involvement of IgE- and non-IgE isotypes in hypersentitivity reactions are confirmed by novel methods for detecting anti-drug antibodies. This manuscript summarizes the current knowledge on factors influencing immunogenicity to biological agents, and points to the mechanisms underlying the drug-induced hypersensitivity reactions.